“Vision 2040” Strategy Of The Sultanate Of Oman: A Model Of Political Modernization And Sustainable Development - Nilufar Nasirova (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article provides an in-depth analysis of Oman’s Vision 2040 as a comprehensive national strategy aimed at political modernization and sustainable development in the context of global economic transformation and regional change. The study examines the conceptual and theoretical foundations of Vision 2040, highlighting its alignment with modern governance theories, sustainable development paradigms, and long-term strategic planning approaches adopted by reform-oriented states. Particular attention is given to the institutional reforms envisaged by the strategy, including the enhancement of public sector efficiency, the strengthening of transparency and accountability mechanisms, and the gradual development of participatory governance within the framework of Oman’s political and cultural traditions. In addition, the article analyzes the socio-economic priorities of Vision 2040, such as economic diversification beyond hydrocarbon dependence, private sector development, human capital investment, innovation-driven growth, and environmental sustainability. The strategy’s emphasis on education reform, labor market modernization, digital transformation, and inclusive social policies is assessed as a means of ensuring long-term economic resilience and social cohesion. The study also considers the role of Vision 2040 in balancing continuity and change by integrating modernization objectives with national identity, social stability, and state legitimacy. Based on a qualitative analytical approach, the article evaluates Vision 2040 as a model of gradual and adaptive political modernization that seeks to reconcile governance reform with sustainable development goals. The findings suggest that Oman’s Vision 2040 represents a structured and forward-looking framework that may serve as a reference point for other states pursuing long-term development strategies under similar political and socio-economic conditions.